EFFECTIVE METHODS OF TEACHING ENGLISH BASED ON THE COMMUNICATIVE APPROACH (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article explores the practical application of the Communicative Language Teaching (CLT) approach in English as a foreign language (EFL) classrooms. It analyzes the role of real-life communication tasks, role-plays, and pair work in developing students’ speaking competence. The results indicate that communicative methods significantly improve learners’ fluency, motivation, and overall language performance compared to traditional grammar-translation methods. The article also provides practical recommendations for EFL teachers